Hate speech and the Political Delegitimization of Women on Social Media: A Critical Discourse Analysis in Digital Political Communication - Abdullah Mitrin; N. Doni Dwi Putra; Rudi Rahman (Communication Studies Program Faculty of Social and Political Sciences Universitas Nurdin Hamzah Jambi, Indonesia, 2026)
This study aims to analyze hate speech as a strategy of political delegitimization against women in digital political communication on social media. In recent years, the increasing participation of women in politics has not always been accompanied by equal acceptance, but rather by the rise of hate speech targeting not only their professional capacity but also their gender identity. This study employs a qualitative approach within a critical paradigm using Critical Discourse Analysis based on the framework of Norman Fairclough to examine how language is used to construct, reproduce, and legitimize gender inequality in digital political communication. The data consist of hate speech content collected from various social media platforms through purposive sampling techniques. The findings reveal that hate speech against women follows systematic discursive patterns characterized by gender stereotypes, the delegitimization of leadership capacity, and the shift of issues from political substance to personal aspects. Furthermore, the construction of gender within hate speech reflects a double standard that positions women as inferior political actors. In this context, hate speech functions not merely as an expression of hostility but as a strategic form of political communication that actively shapes public perception and undermines women’s legitimacy. The implications of this study highlight the importance of a critical approach in understanding the relationship between language, power, and gender, as well as the need for comprehensive efforts to address hate speech through regulation, digital literacy, and the strengthening of ethical political communication in the digital era.